HUMAN PARVO VIRUS B19 IN NIGERIA: A SYSTEMATIC REVIEW AND META-ANALYSIS - Iyanda, Abiodun; Opaleye, Oluyinka O. (FUDMA Journal of Sciences, 2025)
Human Parvovirus B19 is an important pathogen that causes Erythema infectiosum (also known as fifth disease) in children, non-immune hydrops fetalis in pregnant women, aplastic crisis in sickle cell patients, anaemia in immunocompromised patients as well as arthralgia in seronegative immunocompetent individuals worldwide. Many studies on human infection with parvovirus B19 have been reported globally. However, a systematic review and meta-analysis of the infection has not been published in Nigeria. This study extracted articles pertaining to B19V infection in humans in Nigeria using four databases: Google Scholars, PubMed, web science, and African Journals OnLine (AJOL). We retrieved 24 articles related to B19V infection in Nigeria and these articles were retrieved from 1 January 2009 to 20 May 2024. It was estimated that the overall prevalence of humans with parvovirus B19 in the selected period was 25.9% (1377/4275). In the subgroup analysis, the prevalence of B19V was estimated to be 66.9%, 46.7%, 40.6%, 26.7% and 13.5% in the North West, North East, North Central, South South and South West of Nigeria, respectively. In sickle cell patients, the prevalence of B19 V was 34.2%. (17.7-57.0). By contrast, the prevalence of B19V in HIV patients was only 3.3%. (0.7-14.8). The prevalence of parvovirus B19 infection in pregnant women, sickle cell patients, children, blood donors, HIV patients, and hepatitis patients in Nigeria was found to be significantly different in the current review. It is recommended that periodic infection screening be incorporated into the routine clinical care of these patients.